1996
DOI: 10.2307/2787021
|View full text |Cite
|
Sign up to set email alerts
|

Double Standards in the Evaluation of Men and Women

Abstract: Each copy of any part of a JSTOR transmission must contain the same copyright notice that appears on the screen or printed page of such transmission. JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
254
1
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(272 citation statements)
references
References 26 publications
10
254
1
7
Order By: Relevance
“…Foschi's (1992Foschi's ( , 1996Foschi's ( , 2000 theory about double standards for competence is also relevant to this issue. According to Foschi, different standards are used in scrutinizing equal performance by a man and a woman to make judgments about competence, with performance by members of lower status groups (e.g., women) assessed by stricter standards than similar performance by members of higher status groups (e.g., men).…”
Section: Performance Evaluation and Promotionmentioning
confidence: 99%
“…Foschi's (1992Foschi's ( , 1996Foschi's ( , 2000 theory about double standards for competence is also relevant to this issue. According to Foschi, different standards are used in scrutinizing equal performance by a man and a woman to make judgments about competence, with performance by members of lower status groups (e.g., women) assessed by stricter standards than similar performance by members of higher status groups (e.g., men).…”
Section: Performance Evaluation and Promotionmentioning
confidence: 99%
“…Glass, 1990;England et al, 1994). Research has also demonstrated the existence of a double standard in the evaluation of the work done by men and women, through which equal job tasks are more highly appraised when done by men than when done by women (Bose and Rossi, 1983;McArthur, 1985;Foschi, 1996). If the work commonly performed by women is undervalued with respect to the work commonly performed by men, individuals working in female-dominated occupations will have less power in the bargaining process which precedes household migration ceteris paribus.…”
Section: -The Effects Of Occupational Sex-segregation On Family Migramentioning
confidence: 99%
“…Men's stronger interest in and greater likelihood of persistence in STEM fields is also driven by gender-differentiated self-perceptions of fit and ability (Cheryan et al 2009;Wynn and Correll 2017) and the application of double standards for competence Foschi 1996). Both of these mechanisms arise from the mismatch between expectations for STEM workers and expectations for women's behavior.…”
Section: Stereotype Content and Inequality In Stemmentioning
confidence: 99%
“…On the demand side, the most obvious intermediary mechanisms are discrimination against workers and applicants whose gender does not "fit," or align with, the gender of the job, gendered recruitment practices, and biased assessments of individuals' relative qualifications (Becker 1957;Phelps 1980;Bielby and Baron 1986;Foschi 1996;Heilman 2001). On the supply side, stereotyping reinforces segregation by leading people to make gender-conforming choices that affirm their masculinity or femininity, and avoid social sanctions and discriminatory work environments (West and Zimmerman 1987;Ridgeway 2011;Cech 2013;Blair-Loy et al 2017;Weisgram and Diekman 2017).…”
Section: Micro-macro Interactions: Cultural Stereotypes Into Aspirationsmentioning
confidence: 99%